A case of neutrophilic dermatosis with MEFV gene variant and abnormal activation of peripheral blood monocytes: a case report. Issue 1 (2nd January 2019) - Otsuka, Mizuna; Koga, Tomohiro; Sumiyoshi, Remi; Koike, Yuta; Furukawa, Kaori; Okamoto, Momoko; Endo, Yushiro; Tsuji, Sosuke; Takatani, Ayuko; Shimizu, Toshimasa; Igawa, Takashi; Kawashiri, Shin-Ya; et al.
Abstract: A healthy 32-year-old man had a fever and elevated levels of white blood cells (WBC) and C-reactive protein (CRP). In addition, he presented with a skin rash on his forehead, around the neck, and from the anterior chest to the abdomen. His laboratory findings showed elevated levels of hepatic enzyme, CRP, and ferritin; therefore, he was suspected to have adult-onset Still's disease (AOSD) and referred to our department. We ruled out hematological malignancy and established diagnosis of AOSD according to Yamaguchi's criteria and treated with 20 mg/day prednisolone. His clinical condition did not improve, therefore, we increased the dosage of prednisolone to 40 mg/day; however, his rash gradually expanded with papules and plaques. A cervical skin biopsy revealed neutrophil dermatosis and analysis of the MEFV gene revealed a heterozygous variant in exon 2 (E148Q). We found an elevated percentage of CD86 + CD14 + CD16 – classical monocytes in the peripheral blood using flow cytometry. We added oral potassium iodide as a treatment for neutrophil dermatosis. Despite this treatment, his eruption and fever did not subside, therefore, we changed potassium iodide to colchicine, this improved his clinical condition. This case suggests the importance of autoinflammation-related gene abnormalities and macrophage activation in the pathogenesis of neutrophil dermatosis.